Landscape Planning and Design of Urban Rivers with Environmental Approach (Case Study: Farahzad River Valley in Tehran) - Zahra Sadrazamnouri; Jafar Nouri; Farah Habib; Mojtaba Rafieian (علوم محیطی)
Background and Objectives: Urban river valleys are natural corridors and aquatic habitats which provide an enlivening landscape for the cities and also they play an important role towards environmental, social, and cultural issues for urban residents and development in urban resident's life and development in their area. At the present time, structure and function of these valuable elements have been ruined due to non-planning growth and regardless to environmental subjects in municipal management and landscape planning that they have been converted to the runoff canal network or effluent. Several projects including restoration and rehabilitation of urban rivers have been defined to enhance environment of the city in Tehran. One of the weaknesses of urban management is distinguished just one dimension view towards development and even restoration. There are some solutions that can almost provide an ecologically sustainable condition for the river although the ability to return to the original state has been deprived. Implementation of engineering and managerial methods in compound and consideration of various dimensions of management are the main targets of this study, so land-use planning for the area around the river is applying as a suitable tool to restore and return it from a flooding area to a precious natural resource and servicing system. Of course, the objectives will obviously be reached if the key elements comprising ecology, economic, socio-culture, land-use, and executive and their subset indices have been considered in an integrating manner. In order to apply compound methods and presenting subjective results, Farahzad River Valley was selected as a case study. Methodology: Geographic Information System (GIS) and Urban River Survey (URS) were used to illustrate and classify sustainable ecological indices, respectively. At first, river area divided to 8 stretch in 50 meters then initial environmental indices including materials, habitat features, and flora were combined together and the features of each stretch were identified. Using cluster analysis, the values of initial indices were classified and entered in SPSS software. Therefore, the stretches were ranked from very good to poor in the various classes. Results and discussion: In overall, Farahzad River area were zoned in 4 qualitative classes, very good, good, moderate, and under moderate for landscape design. In the northern section of Farahzad River which is in the Kan Basin, about 32 percent of Farahzad River was situated in the very good class in terms of environmental indices. The very good class area was located in the mountain region. Because of the green spaces and gardens, approximately 11 percent was distinguished in good class. Both very good and good areas showed the potential for restoration and management of the river in these sectors. Nearly 12 percent of river stretch was classified in moderate level and other parts belong to moderate level. In the southern section of Farahzad River area which is located in the central catchment, the whole area was assessed in the under moderate level. That means probably it is possible for to define suitable land-uses gradually and design future landscape, with low changes. Conclusion: Ultimately, sustainable recreation with river rehabilitation approach was distinguished as the best land-use of Farahzad River Valley Stretch that can considerably be implemented in the northern parts of the river and green space areas. Then, a thorough planning based on the holistic and integrated approach is required an account of river protection and rehabilitation if it is possible for the downstream parts, after Western Flood Control Canal where is under pressure by urban development.